First report of Black Spot on Eucalyptus grandis × Eucalyptus urophylla caused by Pseudoplagiostoma eucalypti in Guangxi, China - Cao, Xiuxiu (Plant disease, 2023)
Eucalyptus grandis × Eucalyptus urophylla hybrid clone is an economically and ecologically important forest variety and is widely planted in Guangxi, China. Black spot, a newly found disease, occurred nearly 5333.3 hectares in an E. grandis × E. urophylla plantation of Qinlian forest farm (N: 21.866°, E: 108.921°) in Guangxi in October, 2019. Infected plants had lesions of black spots with watery margins on petioles and veins of E. grandis × E. urophylla. The size of spots ranged between 3 to 5 mm in diameter. When lesions expanded to girdle the petioles, wilt and death of leaves was observed, which subsequently affected growth of the trees. To isolate the causal agent, symptomatic plant tissues (leaves and petioles) were collected from two different sites, sampled from five plants each site. In the lab, infected tissues were surface sterilized with 75% ethanol for 10 seconds, then 2% sodium hypochlorite for 120 seconds, and rinsed with sterile distilled water three times. Small segments (5×5 mm) were cut from the margins of the lesions, then placed on potato dextrose agar (PDA) plates. The plates were incubated at 26°C in dark for 7 to 10 days. Fungal isolates YJ1 and YM6 with a similar morphology, which were obtained from 14 of 60 petioles and 19 of 60 veins respectively. These two colonies were initially light orange, then turned to olive brown as time progressed. Conidia were hyaline, smooth, aseptate, ellipsoidal, apex obtuse, and base tapering to flat protruding scar, 16.8 to 26.5µm long, and 6.6 to 10.4 µm wide (n=50). Some conidia had one or two guttules. The morphological characteristics were consistent with the description of Pseudoplagiostoma eucalypti Cheew., M. J. Wingf. & Crous (Cheewangkoon et al. 2010). For molecular identification, the internal transcribed spacer (ITS), β-tubulin (TUB2) genes were amplified using primers ITS1/ITS4 and T1/Bt2b, respectively (White et al. 1990; O'Donnell et al.1998; Glass and Donaldson 1995). Sequences of the two strains were deposited in GenBank (ITS: MT801070 and MT801071; BT2: MT829072 and MT829073). Phylogenetic tree was constructed with a maximum likelihood method, revealing that YJ1 and YM6 were on the same branch with P. eucalypti. Pathogenicity tests of the two strains were performed on three-month-old E. grandis × E. urophylla seedlings, by inoculating 6 wounded (by stabbing on petioles or veins) leaves of seedlings with mycelial PDA plugs (5 ×5 mm) from the edge of a 10-day old colony of strain YJ1 or YM6. Another 6 leaves were treated in the same manner but with PDA plugs as controls. All treatments were incubated in humidity chambers at 27°C and 80% relative humidity, under ambient light. All experiments were conducted three times. Lesions were observed at the points of inoculation, the petioles or veins turned black on inoculated leaves after 7 days, wilting of the leaves were also observed after 30 days, however the controls remained asymptomatic. Re-isolation was made and the fungus had same morphological measurements as the inoculated fungus, thus completing Koch's postulates. P. eucalypti had been reported as a pathogen of leaf spot on E. robusta in Taiwan island (Wang et al. 2016), leaf and shoot blight on E. pulverulenta in Japan (Inuma et al. 2015). To our knowledge, this is the first report of P. eucalypti affecting E. grandis × E. urophylla in mainland China. This report provides basis for the rational prevention and control of this new disease in the cultivation process of E. grandis × E. urophylla